Life Sciences Teacher’s Perspectives on Instructional Leadership: A Case of Two South African Schools - Thobile Perseverance Madonsela; Loyiso Jita; Olalekan Badmus (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2025)
Abstract: Student performance and achievement have always been at the centre of school reform efforts around the world. This led to Instructional Leadership being regarded as being key for improving teaching and learning processes. Although there is an inextricable connection between instruction and learning, it does not directly address subject-specific Instructional Leadership. Hence, this study investigated teachers' perspectives on Instructional Leadership for the subject of Life Sciences. By applying a qualitative case study approach, we interviewed high school principals, departmental heads, and teachers in two South African schools from the Gert Sibande District in the Mpumalanga Province. Thematic analysis was employed to analyse the collected data. Findings revealed differences in the conception and understanding of Instructional Leadership among teachers, departmental heads, and principals regarding the Life Sciences. Teachers only understood Instructional Leadership based on their job-descriptions. We recommend that based on the findings of this study, it is important that the knowledge of teachers, departmental heads and principals be extensively upgraded on subject-specific Instructional Leadership. Keywords: Academic achievement, Instructional Leadership, Life Sciences, supervision, transition